Effects of a muscular stretching and strengthening school-based exercise program on posture, trunk mobility, and musculoskeletal pain among elementary schoolchildren - a randomized controlled trial - Mariana Vieira Batistão; Letícia Carnaz; Roberta de Fátima Carreira Moreira; Tatiana de Oliveira Sato (Editora Champagnat, 2019)
Abstract Introduction: The exercise benefits for the most prevalent postural changes require proper investigation, with large samples, control group, and concealed allocation. Objective: To assess the effects of a muscular stretching and strengthening school-based exercise program on posture, trunk mobility, and musculoskeletal pain among elementary schoolchildren. Method: Three hundred students from three schools in Brazil were evaluated. Stretching and strengthening exercises, twice a week, for eight weeks in group sessions were provided by one physiotherapist. The control group did not undergo any intervention. Head, back and shoulder posture were qualitatively evaluated. Head and trunk alignment were evaluated using the Posture Assessment Software. Cervical, thoracic, low back and upper limb pain were assessed for the last seven days. The trunk mobility was recorded through the flexibility of the posterior chain. Posture, pain and trunk mobility were recorded at baseline and after the intervention. Groups were compared using χ2 test, two-way MANOVA, and two-way ANOVA, with α set at 5%. Results: Shoulder posture showed significant results (P = 0.04), the intervention group showed the lower worsening rate. In the quantitative evaluation, a statistically significant difference was observed between assessments (P < 0.01 for head and trunk; ES = 0.53) but not between groups. The intervention group had a higher percentage of improvement in the overall musculoskeletal pain (P = 0.04; ES = 0.54). Mobility decreased an average of 1.8° in the control group and increased 5.0° in the intervention group, without statistical significance. Conclusion: The program was effective in reducing pain level and shoulder misalignment at the intervention group.